Analysis of Problems and Prospects for Improving Automatic Control Systems of Interconnected Electric Drives - Nalibayev, Nurgali; Kozhageldi, Bolat; Omarov, Zhaksylyk; Zhanpeiissova, Aizhan; Tashimbetov, Murat (Universitas Muhammadiyah Yogyakarta, 2024)
The aim of this study was to analyse the problems and prospects for improving automatic control systems of interconnected electric drives. Various methods, including analytical, classification, functional, statistical, and synthesis, were used to provide recommendations for error correction in the design processes of these systems and to detail their functioning. The study revealed the peculiarities and differences of automatic control systems of interconnected electric drives. The study analysed the errors made during the operation of these systems and the reasons for their occurrence. It also identified uncertainties in the development process and their impact on the functioning of the systems. The mechanism's efficiency, development, and complexity in different spheres were analysed. The text also considered issues related to estimating the operation of systems, limitations during operation, and the influence of limitations on results. Recommendations for promoting more effective regulation have been provided. The research showed that these systems play a crucial role in complex technological processes. The results have vague practical implications for developing the mechanism of automatic control systems for interconnected electric drives to apply and influence a certain device. In conclusion, the study analysed the problems and prospects for improving automatic control systems for interconnected electric drives.